Competitive (versus loyal) showrooming: An application of the push-pull-mooring framework. (September 2021) - Frasquet, Marta; Miquel-Romero, Maria-Jose
Abstract: Showrooming is an increasingly popular practic that threatens retailers' performance. This paper adopts the push-pull-mooring framework to understand the shopper decision to purchase online from a different retailer (competitive showrooming) rather than from the same retailer visited to gather information (loyal showrooming). Going beyond the customer motivation to get the best value, we focus on retailer-situational variables (store crowding and quality of salesperson service) and retailer-relational variables (customer satisfaction, trust and loyalty) in the decision on competitive (vs loyal) showrooming. Data was collected via a survey answered by 659 showroomers and analysed using fuzzy-set Qualitative Comparative Analysis (fsQCA) to unveil different patterns of competitive showrooming. Results highlight the role of mooring factors, such as a strong customer-retailer relationship and quality salespersons' service, in reducing competitive showrooming.